Anaerobic biodegradation of benzene-laden wastewater under mesophilic environment and simultaneous recovery of methane-rich biogas. Issue 2 (April 2018) - Rahman, Wasi Ur; Khan, Mohammad Danish; Khan, Mohammad Zain; Halder, Gopinath
Highlights: Anaerobic digestion of benzene-laden wastewater in mesophilic condition was studied. COD removal efficiency of 85% was achieved under experimental condition. CH4 and CO2 production were higher in glucose dose of 0.08 g in 80 mL sample. Highest amount of CH4 and CO2 produced were 306 μL and 248 μL respectively. Methanogenic activity was found to be 1.8 mM CH4 gVS −1 day −1 using acetate. Abstract: The present investigation emphasizes on the anaerobic biological treatment of benzene containing wastewater under mesophilic temperature towards elimination of chemical oxygen demand (COD) and simultaneous recovery of methane-enriched biogas. The anaerobic degradation of benzene has been examined over the influence of different co-substrates in an anaerobic bioreactor of 100 mL volume. Acetate and glucose are added as co-substrates with a concentration of 1 gL −1 to monitor and compare the methanogenesis during anaerobic digestion. During the experiment, COD removal efficiency of 85% was achieved. Methane (CH4 ) and carbon dioxide (CO2 ) production has been observed to be higher in glucose (1 gL −1 ) fed anaerobic reactor with the highest amount of CH4 (306 μL) and CO2 (248 μL) produced under mesophilic condition (35 ± 1 °C), pH of 6.82, conductivity of 0.073 μS cm −1 and at a concentration of 200 mgL −1 of benzene analysed using gas chromatography coupled with thermal conductivity detector (TCD). Scanning electron microscopy (SEM) analysis demonstrated the high porous structure of anaerobic sludge with uniform channels confirming better mass transfer and high benzene removal. Energy dispersive x-ray (EDX) showed various constituent elements present in the microbial sludge including carbon, oxygen, magnesium, silicon, aluminium, and zinc. The specific methanogenic activity was found to be 1.8 mM CH4 gVS −1 day −1 using acetate as a source of energy. The study reveals that the anaerobic reactor has made possible biogas production and COD removal through efficient degradation of complex substrate like benzene in wastewater.